Hey there!
To solve for the x value of this system of equations, the best choice would be to use substitution since you can solve for y for one of the equations and plug that equation into the y value of the other equation to solve for x.
To start, first solve 6y=x+18 for y:
6y=x+18
y=1/6x+3
Now that you have y set equal to 1/6x+3, plug this expression in place of the y value in -x+2y=6:
y=1/6x+3
-x+2y=6
-x+2(1/6x+3)=6
Now, simplify, and solve for x:
-x+2(1/6x+3)=6
-x+2/6x+6=6
-2/3x+6=6
-2/3x=0
x=0
Therefore, x=0 would be your final answer!
Hope this helps!